Pendekatan Psikologi Islam Dalam Mengembangkan Keterampilan Sosial Anak Melalui Pendidikan Agama Islam Di Kelas 5 Sekolah Dasar Negeri 01 Sumbawa Besar - Jayanti, Dewi; Susanti (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2025)
Approach psychology Islam can create very safe environment and also very supportive. Where students really feel accepted and greatly appreciated. Can reduce stress and also can increase development social students. In research This aiming For can know approach psychology Islam in develop skills social children. As for the method in study This is Qualitative descriptive research is a type of conceptual research that can involve a number of people as sources. And this is in collecting data using qualitative. And as for data collection in research is by interview, observation and also analyzed using thematic analysis. The results of this study are showing the use of visual aids, playing and also telling stories and also using group-based activities. In this case, it can recognize and also manage various emotions and can develop students' empathy, for example managing and recognizing emotions in developing students' social skills.